2014
DOI: 10.1099/jmmcr.0.002022
|View full text |Cite
|
Sign up to set email alerts
|

Kocuria dacryocystitis infection, caused by kocuria ocularis sp. Nov.

Abstract: Introduction: Kocuria spp. rarely cause infectious disease but can be opportunistic pathogens in immunocompromised patients. The numbers of documented infections are low but rising.Case presentation: A 74-year-old woman presented with acute, painful swelling of the medial canthus of the left eye. The skin surface was red and acutely painful to the touch. Because of several clinical relapses despite antibiotic treatment, surgical dacryocystorhinostomy with marsupialization of the lacrimal sac into the nasal cav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…[ 3 ] Several systemic and ocular infections, in the form of keratitis, dacryocystitis, and endophthalmitis have been reported. [ 2 6 7 8 ] Studies have shown this organism to be susceptible to a wide range of antibiotics, but the strain isolated from our patient was multidrug-resistant with sensitivity only to vancomycin, ofloxacin, and linezolid suggesting a variable pattern of susceptibility. [ 4 ] A compromised ocular surface or underlying systemic immunosuppression has been attributed to the pathogenesis of the organism, however, both were absent in our patient including any form of ocular allergy.…”
Section: Discussionmentioning
confidence: 90%
“…[ 3 ] Several systemic and ocular infections, in the form of keratitis, dacryocystitis, and endophthalmitis have been reported. [ 2 6 7 8 ] Studies have shown this organism to be susceptible to a wide range of antibiotics, but the strain isolated from our patient was multidrug-resistant with sensitivity only to vancomycin, ofloxacin, and linezolid suggesting a variable pattern of susceptibility. [ 4 ] A compromised ocular surface or underlying systemic immunosuppression has been attributed to the pathogenesis of the organism, however, both were absent in our patient including any form of ocular allergy.…”
Section: Discussionmentioning
confidence: 90%
“…The constituent genuses Kocuria and Micrococcus were detected in the plates. While both of these taxa are not typically pathogenic, they have been reported as opportunistic infections (Smith et al 1999 ; Mattern and Ding 2014 ; Domont et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…A few reports of human infections, as shown in Table 1, were ascribed to Kocuria species comprising of a case of dacryocystitis due to Kocuria ocularis [3], a case of acute cholecystitis caused by Kocuria kristinae [4], a case of meningitis due to Kocuria rosea [5], a case of brain abscess due to Kocuria varians [6], four cases of infective endocarditis due to K. rosea [7,8], K. kristinae [9,10], seven cases of peritonitis attributing to three Kocuria marina [11,12] and to two K. rosea [13,14], and one case of K. varians [15] and two cases of K. kristinae [16,17], and 21 cases of blood-stream infections attributing to two Kocuria rhizophila [18,19], one K. varians [20], two K. rosea [21,22], to fourteen K. kristinae [9,23e27], to one K. marina [28], and to one Kocuria salsicia [29], respectively. Among the 21 cases of bacteremia (Table 1), the majority cases were catheterrelated blood stream infections.…”
Section: Introductionmentioning
confidence: 98%